A/r/tography: When Ars, Teaching, and Research meet - Alkhudair, Maha Ibrahim (Journal of Educational and Psychological Sciences, 2022)
There are many aspects of educational research in the field of arts, but a/r/tography comes to establish an identity for those who are artists, teachers, and researchers at the same time. The present review article aims to shed light on a/r/tography and reviews its definitions from different aspects, focusing on how it leads exchanges between text and image, and between practice and theory (Irwin et al., 2008). This research also shows how a/r/tographers who live in the in-between spaces are aware that art, research, and teaching are not done, but rather lived (Irwin et al., 2008). A/r/tographers in their research create a dialogue with fellow a/r/tographers recognizing their role and influence on their production. Since a/r/tography is concerned with the teaching process as one of its aspects, the research sheds light on its great impact on students. The research also touched on the applications of a/r/tography in different countries such as Canada, Iran, Australia, Saudi Arabia, and others. It also touched on its applications in different fields of arts such as literature, theater, and visual arts. Due to the flexibility of the methodology of this research, the researcher encourages its application in the Arab world.
Keywords: A/r/tography; Art education; Living inquiry; Art; Contemporary trends